Cortisone and cortisol break hydrogen-bonding rules to make a drug–prodrug solid solution. (2020) - Verma, Vivek; Bordignon, Simone; Chierotti, Michele R.; Lestari, Monica; Lyons, Kieran; Padrela, Luis; Ryan, Kevin M.; Lusi, Matteo
No abstract available